The Effect of Waterpipe Tobacco Smoking on Bone Healing Following Femoral Fractures in Male Rats - Sadeghifar, Amirreza; Sheibani, Mohamad; Joukar, Siyavash; Dabiri, Shahriar; Alavi, Samanehsadat; Azari, Omid; Vosoghi, Darioush; Zeynali, Yas; Zeynali, Yasman; Shahraki, Mohamad; Torghabe, Amirhesam; Rostamzadeh, Farzaneh; et al. (Frontiers in Surgery, 2021)
Background: Given the increasing use of waterpipe tobacco smoking (WTS) in the world and its unknown effects on bone healing, this study investigated the repairing of femoral bone fractures in rats exposed to WTS. Main methods: 40 male Wistar rats were divided into two groups, including the femoral fracture (Fx) and the Fx +WTS groups. Each group was divided into two subgroups that were evaluated for bone healing 28 and 42 days after femoral fracture. After fixing the fractured femur, healing process was evaluated by radiography, pathological indicators and measurement of blood levels of vascular endothelial growth factor (VEGF), Parathyroid hormone (PTH), Ca ++, Transforming growth factor-beta (TGF-β) and Insulin-like growth factor 1 (IGF-1). Also, the density of VEGF and CD34 in fracture tissue was investigated by immunohistochemistry. Key findings: Radiographic findings showed factors related to the earlier stages of bone healing had higher scores in the Fx +WTS28 and 42 subgroups in comparison to Fx groups. Density of VEGF and CD34 showed that the angiogenesis processes was different in the bone fracture area and callus tissue in the Fx +WTS subgroups. Serum levels of VEGF, TGF-β, IGF-1 were significantly lower in Fx +WTS42 group and PTH in the Fx +WTS28 group was higher than the other groups. Significance: The findings showed disturbance and delay in the femoral fractures union in rats exposed to hookah smoke. This is partly due to the reduction of molecular stimuli of bone synthesis as well as the attenuation of quantitative angiogenesis.